Evaluation of peritoneal endometriosis treatment using intralesional acetylsalicylic acid injection in rabbits - Saad-Hossne, Rogério [UNESP]; Barretto, Adriana Beatriz [UNESP]; Siqueira, Juliana Menezes [UNESP]; Denadai, Rafael [UNESP] (FapUNIFESP (SciELO), 2016)
PURPOSE: To investigate the efficacy of intralesional 20% aspirin injection for treatment of experimental peritoneal endometriosis. METHODS: Peritoneal endometriosis was experimentally induced in forty adult nulligravid female rabbits. On day 30 post-endometriosis induction, rabbits were randomly divided to assess early (10 days) and late (20 days) effects of intralesional injection of physiological saline solution (control groups) in comparison to intralesional injection of 20% bicarbonate aspirin solution (experimental groups) as follows: control group 1 (10 days, n=10); control group 2 (20 days, n=10); experimental group 3 (10 days, n=10); experimental group 4 (20 days, n=10). Resected tissues, including endometriosis foci, were qualitatively (general morphology and signs of inflammatory cells infiltrate, necrosis and apoptosis) and quantitatively (remaining endometriosis area) assessed by histopathological analysis. RESULTS: Extensive necrosis, hemorrhage, apoptosis, and fibrosis were observed in the experimental groups 3 and 4. Groups 1 and 2 presented typical endometrial tissue cysts, respectively. Groups 3 and 4 showed sparse endometrial tissue foci and no endometrial tissue, respectively. Quantitative analysis revealed that aspirin-treated groups 3 and 4 had significantly (p<0.05) smaller remaining endometriosis area, compared to control groups 1 and 2. CONCLUSION: Intralesional 20% aspirin injection caused total destruction of peritoneal endometriosis foci in rabbits.
Keywords: Aspirin; Endometriosis; Rabbits